Calculation of Gravitational Acceleration Using the Method of Objects Oscillating at the End of a Spring and Swinging a Pendulum - Marwiyah Nst, Masringgit (Universitas Syiah Kuala, 2024)
Basically, this experiment with a pendulum is inseparable from vibration. In this experiment we will use two methods to calculate the vibration period, namely through an insulated object at the end of the spring and the swing of the pendulum. The results of the vibration period calculation will be compared and analyzed using the two methods and it will be seen which method is more accurate in calculating the spring period. Based on the data obtained from observations, it can be concluded that from the two methods used, determining gravitational acceleration using a pendulum swing is more accurate. This is seen from the average value of gravitational acceleration (g), where we obtain the following values: g pendulum = 9.559 ms2 and g spring = 10.07 ms2. These two values indicate that the g value of the pendulum swing is closer to the general gravitational acceleration value, namely 9.81 ms2